RANCANGAN ALAT PENGATUR SUHU PADA HOME INDUSTRI JAMUR TIRAM DI DESA PINANGRAJA KECAMATAN JATIWANGI KABUPATEN MAJALENGKA - Shobari, Encu; Lugina F Haris, Hegi; Awwaludin Imam M, Yofi (Jurnal Mnemonic, 2018)
In the research conducted several steps carried out in the development of oyster mushrooms themselves, ranging from the selection of good seeds to the deposition or indoor planting, which is still at a temperature 30° C, which when the temperature does not persist will affect the growth of oyster mushroom. Given the temperature in the Pinangraja area itself reaches 32° C Therefore the need for a stable temperature in the oyster space. In its design using the filtering method of the results that come from inside and flowed using the crystals used.